2022
DOI: 10.1097/ftd.0000000000000980
|View full text |Cite
|
Sign up to set email alerts
|

Real-World Comparison of Isavuconazole and Voriconazole in Terms of the Need for Dosage Adjustments Guided by Clinical Pharmacological Advice During Primary Prophylaxis of Invasive Fungal Infections in Pediatric Patients with Hemato-Oncological Malignancies

Abstract: Background:Limited evidence concerning optimal azole dosing regimens currently exists for antifungal prophylaxis in hemato-oncological pediatric patients.Methods:Hemato-oncological children receiving intravenous or oral isavuconazole or voriconazole for primary antifungal prophylaxis at IRCCS Azienda Ospedaliero–Universitaria of Bologna during November 2020 to October 2021 and undergoing CPA programs based on real-time therapeutic drug monitoring (TDM) were retrospectively analyzed. CPAs for isavuconazole and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…Isavuconazole at the studied dose of 10 mg/kg was generally well tolerated and showed an overall safety profile similar to that observed in adults; moreover, plasma drug exposure was comparable to that observed in adults in phase 3 efficacy trials [ 107 ]. More recent data [ 108 ] suggested that the variability of isavuconazole exposure in hematological pediatric patients could be low: the analysis of 16 patients showed that dosage adjustment for isavuconazole was required in 3.3% of cases ( p < 0.001) and at the first real-time therapeutic drug monitoring, the reach of the desired target was higher for isavuconazole than voriconazole (83.3% vs. 10%, p = 0.008) [ 105 ].…”
Section: Novel Drugs For Contrasting Invasive Fungal Diseasesmentioning
confidence: 99%
“…Isavuconazole at the studied dose of 10 mg/kg was generally well tolerated and showed an overall safety profile similar to that observed in adults; moreover, plasma drug exposure was comparable to that observed in adults in phase 3 efficacy trials [ 107 ]. More recent data [ 108 ] suggested that the variability of isavuconazole exposure in hematological pediatric patients could be low: the analysis of 16 patients showed that dosage adjustment for isavuconazole was required in 3.3% of cases ( p < 0.001) and at the first real-time therapeutic drug monitoring, the reach of the desired target was higher for isavuconazole than voriconazole (83.3% vs. 10%, p = 0.008) [ 105 ].…”
Section: Novel Drugs For Contrasting Invasive Fungal Diseasesmentioning
confidence: 99%